(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In the world of computer applications authentication is the main process of granting access for an individual to get control over the services provided by different service providers. It is the process of identification of particular individual, unique username and password are used. Username and text-based password are the most commonly used technique in authentication, use of this technique is very popular in web applications. Lots of work has been done in the field of authentication. Conventional technique includes the text-based password, which is the combination of alphanumeric letters. On the other side of the authentication Graphical Password techniques are popular among handheld devices, the main motivation behind developing such kind of authentication technique is to provide strong but easy to remember password. Graphical authentication schemes are in use from decades, they have some limitations in early days, but comparatively the schemes which are in use today are secure and trust worthy. In this paper a technique for graphical authentication has been proposed based on the previous work, which can be implemented on the web application. The proposed authentication scheme is made secure using the homomorphic encryption technique to avoid the security issue in database.